Diversification dynamics of chameleons (Chamaeleonidae) - Kevin Arbuckle (Journal of Zoology, 2022)
Chameleons are charismatic and common lizards across Madagascar, Africa, and some surrounding regions. Little is known about their diversification dynamics and how this relates to their ecology, so we estimated diversification rate variation and consider this in the context of three hypotheses previously proposed in the literature. First, that the transoceanic dispersal from Africa to Madagascar on two separate occasions has resulted in fast radiation of Malagasy chameleons. Second, that the substantial floral turnover in their distributions within South Africa has resulted in rapid radiations of the endemic dwarf chameleons (Bradypodion). Finally, that the evolution of distinct ecomorphs of chameleon has fuelled fast diversification via adaptive radiations. We use the most recent and complete phylogeny of chameleons to estimate the diversification dynamics of the group using three methods: BAMM (which estimates constant or gradually changing diversification regimes and tests for shifts in these), MEDUSA (which tests for rate shifts in particular clades), and ClaDS (which estimates branch-specific diversification rates). Our results from all analyses estimate a diversification rate increase in a clade containing most of the genus Bradypodion, a group containing the South African dwarf chameleons which occur in recognized biodiversity hotspots in diverse habitats. We find no evidence for shifts resulting from dispersal events to Madagascar or related to the strong ecomorphological divergence of short-tailed chameleon lineages (Brookesia, Palleon, Rhampholeon, and Rieppeleon). The single burst of diversification within chameleons was in a clade which was associated with geographic areas which have experienced rapid habitat turnover and vicariance over the last ~10 million years. This suggests that ‘habitat vicariance’ resulting from ecological changes in vegetation has contributed to the diversity of species in this area by increasing diversification rates.